1995
DOI: 10.1002/eji.1830250935
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocytes raised against a subdominant epitope offered as a synthetic peptide eradicate human papillomavirus type 16‐induced tumors

Abstract: Cytotoxic T lymphocytes raised against a subdominanl epitope offered as a synthetic peptide eradicate human papillomavirus type 16-induced tumorsPreviously, we have shown that immunization with human papillomavirus (HPV) type 16-derived cytotoxic T lymphocyte (CTL) epitope E7 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 30 publications
1
79
0
Order By: Relevance
“…In contrast, the tumor models utilized in this study are at least mildly immunogenic (24JK-FBP) or known to be highly immunogenic (C3). 33,34,35 Although the 24JK-FBP line was derived by retroviral transfection of human folate-binding protein into the lowly immunogenic 24JK parental line, 36 the immunogenicity of the resultant 24JK-FBP line is not known. However, the immunogenicity of 24JK-FBP is almost certain to be increased, compared with the parental line, due to stable integration of the retroviral genes and human FBP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the tumor models utilized in this study are at least mildly immunogenic (24JK-FBP) or known to be highly immunogenic (C3). 33,34,35 Although the 24JK-FBP line was derived by retroviral transfection of human folate-binding protein into the lowly immunogenic 24JK parental line, 36 the immunogenicity of the resultant 24JK-FBP line is not known. However, the immunogenicity of 24JK-FBP is almost certain to be increased, compared with the parental line, due to stable integration of the retroviral genes and human FBP.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 HPV E6 and E7 proteins, constitutively expressed in HPV-transformed cells, are considered to be tumor-specific antigens that can act as targets for cytotoxic T lymphocyte (CTL)-mediated tumor cell killing and stimulation of tumor-specific CTL activity. [4][5][6][7] The induction of class I MHC-restricted CTL activity is optimally achieved by synthesis of viral antigens within antigen presenting cells (APCs), for example through immunization with live attenuated virus. However, apart from its potential risk, this is at present not an option for immunization against HPV infection since the virus cannot be successfully propagated to yield virus particles.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Major drawbacks associated with a peptidebased approach include the problem of MHC polymorphism and the risk of inducing T cell tolerance rather than T cell activation. Due to the induction of specific T cell tolerance, vaccination with a tumor-specific peptide…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In several animal models it has been demonstrated that the HPV E6 and E7 proteins, constitutively expressed in HPV-transformed cells, can act as targets for CTL-mediated tumor cell killing and stimulation of tumor-specific CTL activity. [9][10][11][12] Induction of an antigen-specific CTL response requires intracellular processing of the target antigen and presentation of antigenic peptides by MHC class I molecules. This can be achieved efficiently with recombinant viral vectors.…”
Section: Introductionmentioning
confidence: 99%